Theoretical Analysis of the Relationship Between Contact Stress on Rough Tooth Surface and Gear Speed - Tao Kun; Qi Xiumei; Gao Chuangkuan (Jixie chuandong)
The surface roughness data of test-piece with transverse roughness profiles are measured.With the help of the Fourier approximation,the measured data are used to form a roughness function which is then added to the oil film thickness equation and a model of mixed elastohydrodynamic lubrication for an involute spur gear transmission is established. Based on this model,nearly 130 groups numerical calculations are carried out through changing the pinion speeds for medium and heavy-duty gear transmissions respectively.The computing results show increasing the pinion speed can effectively improve the gearing lubrication state and reduce the contact stress on rough surface. However,decreasing of the contact stress is very slowly with the addition of the pinion speed when the speed exceeds a certain value.